Efek Angiogenesis Beraprost terhadap Gambaran Histopatologi Jantung Tikus Galur Wistar Hipertensi (Angiogenesis Effect of Beraprost on the Cardiac Histopathology of Hypertensive Wistar Rat) - Cynthia Damayanti; Suryono Suryono; Arief Suseno (Pustaka Kesehatan, 2015)
Hypertension is a state where there is an increase of blood pressure above normal threshold,120/80 mmHg. The phatophysiology of hypertension involves the changes of vascular structure. Therefore, the beraprost drug was created. It is a vasodilator and antitrombolytic which is able to induce angiogenesis. The study aimed to investigate the effect of Beraprost on angiogenesis as a hypertension therapy agent. In true experimental design, 22 males wistar rat were divided into control group and treatment group (Beraprost 100mcg/KgBW/day). The results showed that the systolic blood pressure decrease after therapy with Beraprost from 180 mmHg to 143 mmHg whereas diastolic blood pressure consistant at 80 mmHg after induction of hypertension as well as therapy of Beraprost. An examination of cardiac histopathology, there was an increasing number of blood vessels in the treatment group, 16.637.29 compared to 7.45 1.21 in control group. It can be concluded that Beraprost had an angiogenesis effect and decrease systolic blood pressure in hypertensive rat model. Keyword : Hypertension, Beraprost, vascular structure, angiogenesis.